(untitled) (Praxis Educativa, 2017)
For Hannah Arendt the human duty has three fundamental activities that allow people to have a space of life in this planet, the labour: (attention to the basic needs of biological order, the labour, as work, (transformation of objects, materials: objects creation) and action (continual moment to develop the closest capacity of human being: To be free). Taking into consideration the previous information this work is analyzed beginning from the metaphor of plurality and the polyphony of voices. The philosopher searches to give back to the subject its capacity of management its “apparition” in the polis ground. In this sense the article epitomized the theme of the educational ground